PDCD1 polymorphisms are not associated with Takayasu's arteritis in Turkey - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2012)
Objectives. Takayasu's arteritis (TA) is a chronic arterial inflammation of unknown etiology involving mainly the aorta and its major branches. Based on the associations of programmed death-1 (PD-1) protein encoding gene (PDCD1) with connective tissue diseases and vasculitides, PDCD1 polymorphisms are studied for susceptibility to TA in this study. Methods. The study group is made up of TA patients (n=229) fulfilling the 1990 ACR classification criteria and compared to 193 healthy controls (HC). PD-1.3, PD-1.5 and PD-1.6 single nucleotide polymorphisms of PDCD1 gene are genotyped by polymerase chain reaction and restriction analysis (PCR-RFLP). Results. The distribution of PD-1.5 polymorphism in TA patients and HC revealed a similar presence of TT genotype in patients and controls (13.3% vs. 11.4%). PD-1.3 and PD-1.6 were less polymorphic and did not differ between the groups. Rare AA genotype of PD-1.3 (1.4% vs. 1.0%) and AG genotype of PD-1.6 was again similarly (22.4% vs. 19.2%) present in TA and HC. Conclusion. PD-1.3, 1.5 and 1.6 polymorphisms of PDCD1 gene, which were shown to be associated with various autoimmune disorders and vasculitides, are not associated with a susceptibility to TA in Turkish population.
Keywords: Takayasu's arteritis; PDCD1; programmed cell death; RHEUMATOID-ARTHRITIS; GENE POLYMORPHISM; ANKYLOSING-SPONDYLITIS; SUSCEPTIBILITY; CELLS; PD-1; EXPRESSION; DISEASE; ALLELE; TISSUE